Experimental Study of the PVTX Properties of the System H₂O-CH₄ - Lin, Fang (Virginia Tech, 2005)
The system HO-CH is found in a variety of geological environments in the earths crust, from sedimentary basins to low grade metamorphic terrains. Knowledge of the PressureVolume-Temperature-Composition (PVTX) properties of the HO-CH system is necessary to understand the role that these fluids play in different geological environments. In this study the properties of the HO-CH fluid system at elevated temperatures and pressures has been investigated experimentally to determine the PVTX properties of HO-CH fluids in the P-T range equivalent to late diagenetic to low grade metamorphic environments, and XCH4mol%. A study has also been conducted to determine methane hydrate stability over the temperature range of -40~20°C. Synthetic fluid inclusions were employed in both studies as miniature autoclaves. Experimental data for the PVTX properties of HO-CH fluids under late diagenetic to low grade metamorphic conditions was used to calculate the slopes of isoTh lines (the line connecting the P-T conditions of the inclusions at formation and at homogenization) at different PTX conditions. An empirical equation to describe the slope of iso-Th line as a function of homogenization temperature and fluid composition was developed. The equation is applicable to natural HO-CH fluid inclusions up to 500°C and 3 kilobars, for fluid compositions 4 mol% CH. The Raman peak position of CH gas is a function of the pressure and temperature. This relationship was used to determine the pressure along the methane hydrate stability curve in the HO-CH system. The combined synthetic fluid inclusion, microthermometry and Raman spectroscopy method is a novel experimental approach to determine the P-T stability conditions of methane hydrates. The method is fast compared to conventional methods, and has the potential to be applied to study other gas hydrate systems. Ph. D.